An efficient hybrid biomechanical energy harvesting system using human motions for low-power applications - Mohankumar Venugopal; Govindanayakanapalya Venkatagiriyappa Jayaramaiah (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The biomechanical energy harvesting system (BM-EHS) uses human daily activities to create electricity. The BM-EHS is one of the potential alternative technologies for powering wearable and implantable electronic gadgets without batteries. The hybrid BH-EHS is modeled using two different vibration source-based human activities in this manuscript. The piezoelectric (PE) and electromagnetic (EM) based EHS are combined in the hybrid BM-EHS. The PE- EHS is based on human walking and jagging motions and is represented using a mass-spring-damper system and PE stack. The EM- EHS is based on the human knee and hip motions, with shaft conversion and a DC motor. The PE, EM, and hybrid BM-based EHS are modeled using MATLAB/Simulink, and performance results are realized individually. The PE-EHS obtains the average output voltage of 0.5 V and harvests 53.18 mW of power. Similarly, the EM-EHS achieves the average load voltage of 0.567 V and 30.6 mW harvested power. The hybrid BM-EHS obtains the average load voltage of 0.79 V and harvests 86 mW of power. The proposed BM-EHS is compared with the existing EHS with better-harvested power and energy improvement for the given load conditions. Overall, the harvested power can power up the low-power applications.